[quotation] 'The bread which we produce - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
'The bread which we produce by the sweat of our brows is better for our bodies because it frees our conscience, it illustrates the self-respect of the developing countries and it establishes true equality between peoples, between men'.Alioune Diop,...